Clinico-Epidemiological Study of Snake in Chittagong Medical College Hospital, Chattogram - Rahman Chowdhury, Mohammad Mahmudur; Karim, Mohammed Maksudul; Dutta, Hiranmoy; Shafatujjahan,; Sirajum Munir, Abu Saleh Mohammed; Islam, Mohammed Jahedul; Azam, Akramul; Islam, Muhammad Rashedul (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Snakebite is one of the neglected tropical diseases that World Health Organization aimed to halve the numbers of deaths and cases of serious disability by 2030. This study was carried out to describe the epidemiology, clinical features, complications, and the outcome of snakebites which were seen in a tertiary care hospital of Chattogram, Bangladesh. Materials and methods: This observational study was conducted at Snake Bite Clinic of Chittagong Medical College Hospital, Chattogram from October 2010 to March 2011. Three hundred consecutive admitted patients with a history of snake bite were included in the study. A structured questionnaire was used to collect data. Patients were routinely managed in the ward and were followed daily to observe any complications develop and in hospital outcomes were noted. Results: Three hundred cases (n=300) from both gender were included with male to female ratio was 1.3:1. The included patients were with a Median age of 27 (1-65) years. Cases were mostly from Patiya 22.4%, Raozan 9%, Hathazari 8%, Boalkhali 7.4%, Rangunia 6.6% and 5.2% Chandanaish Upazila. Fang/teeth marks were noted in 90.6% cases and majorities were bitten below knee. About half of the victims received some sorts of management within 2 hours of bite including 16% from traditional healer (Ozahs). Most (72%) bites were non-venomous. Among the venomous bite 24% labeled as suspected viper bites having local envenomation sign and 4% bites presented with neuroparalytic symptoms. The symptoms of envenomation included local signs of inflammation (50%) blisters and necrosis (7.4%) ptosis and opthalmoplegia (3%) dysphagia (3.7%) dysphonia (3%) and broken neck sign (3%). Twelve (4%) snake-bite patients received antivenom and two of them developed anaphylaxis. No fatality was observed in the cohort. Conclusions: Most patients admitted in this tertiary care hospital with a history of snake bite had no feature of envenomation and had favorable outcome. The ready availability and appropriate use of antivenom, close monitoring of patients and early referral to a larger hospital all help to reduce the mortality. As majority patients were admitted with no features of envenomation District or Upazila level hospitals could arrange for management of those patient and only patients who needed multidisciplinary care could be referred. Henceforth primary and secondary care level hospitals could be engaged in snake bite management. JCMCTA 2020 ; 31 (2) : 37-42